IMPLEMENTASI PERATURAN BUPATI NOMOR 28 TAHUN 2014 TENTANG IZIN PENGGUNAAN KIOS DAN LOS DI PASAR BATANG, KABUPATEN BATANG - Tanti Anggita Putri; Aloysius Rengga (Journal of Public Policy and Management Review, 2019)
This study aims to describe the implementation of regent regulation number 28 year 2014 concerning kios and los usage permits in the Batang market in Batang regency and also to find out the factors that inhibit and encourage the implementation of regent regulation number 28 year 2014. The locus used in this study is in the Batang market area in Batang regency. This study uses descriptive qualitative research methods. The results of the study show that in implementing the regent’s regulation it was found that the phenomenon of policy accuracy, the accuracy of the implementers, the accuracy of the environment and the accuracy of the process were still considered to be not right. The implementation of regent regulatin number 28 year 2014 concerning kios and los usage permits in the Batang market is still facing obstacles. The driving factors for implementatin include : bureaucratic structure, while the inhibiting factors are in communication, resources, and disposition factors. The conclusion in this study is that the implementation of regent regulation number 28 year 2014 concerning kios and los usage permits in Batang market is still faces obstacles, especially seen from the traders who break the rules such as transferring or stopping the kios or los to others without knowledge from the head of the market, the abandonment of kios and los the lack of awareness of the merchant community about market cleanliness. The based on these conclusions, the researchers recommended to the goverment to increase the intensity of the dissemination of regent regulations, community empowerment, strengthening coordination between implementing parties, adding human resources, cooperation with other parties such as the private sector in order to reduce the lack of budget